Strategies for Strengthening Management Information Systems to Improve Customer Satisfaction in Motor Vehicle Type Testing Services at BPLJSKB Bekasi - Angelina Wahyu Christyani; Tiara Ayustian; Dwi Prasetyo Sayoto Putro; Femmy Sofie Schouten (Dinasti Review, 2026)
Digital transformation in vehicle type approval services at Balai Pengujian Laik Jalan dan Sertifikasi Kendaraan Bermotor (BPLJSKB) Bekasi is reflected in the use of Vehicle Type Approval (VTA) Online. This study aims to analyze management information system strengthening strategies to improve customer satisfaction in motor vehicle type testing services. A qualitative descriptive approach was applied through document analysis and literature review using the DeLone and McLean Information System Success Model and SERVQUAL. The results indicate that VTA Online supports broader access, faster administrative processes, clearer status monitoring, and better service documentation. However, service performance has not been fully optimized because manual and digital procedures still operate in parallel, laboratory data are not fully integrated, information technology infrastructure remains uneven, and the digital competence of service personnel needs further improvement. The proposed strategies include laboratory data integration, platform and procedure standardization, digital competency development, infrastructure modernization, customer-oriented helpdesk services, and periodic monitoring and evaluation. These strategies are expected to strengthen service reliability, transparency, data accuracy, and sustainable customer satisfaction.